Modo de cuidar do lixo eletroeletrônico: analisando mudanças na ação dos estudantes em oficinas ambientais na escola de ensino médio Lauro Rebouças de Oliveira em Limoeiro do Norte-CE - Castro, Maria do Socorro Santos de Assis (Universidade Federal Rural do Semi-Árido, 2017)
This research examines together with students from the state public school Lauro Rebouças de Oliveira de Limoeiro do Norte-Ce, the changes in the coordinations of actions in an environmental education experience focused on the disposal and treatment of electronic and electronic garbage in school. Electrical and electronic waste grows disorderly every day as a consequence of the changes in our society, when the relations human being - technical object happen amid the integration of increasingly powerful digital technologies in the various daily actions. It is a particularly dangerous, toxic waste and therefore harmful to the environment and human health, so it is crucial to focus the research intervention on environmental education in the e-waste issue, because it involves the relationship man-nature that is Essential for the well-being of all humanity. (SOUSA, 2009) This differentiated look that we are launching for this reality makes us perceive the world as an integrated whole, where the subjects recognize themselves as part of the environment. The theoretical support network of research is supported by the studies of Tundisi (1997) and Carvalho (1991), constructions on the problem of garbage and environmental education; And Simondon (1989), philosopher and physicist, a classic that helps us to situate the relation between the processes of human, technical and physical individuation in the configuration of the set we call society. The main objective of the research is to analyze the coordinations of the actions of students of a public high school about an experience of gathering the electroelectronic and to deepen the study on the destination of this garbage in the municipality of Limoeiro do Norte.The methodology chosen for development is the intervention research of a qualitative nature and we will use the Jean Paul Thibaud (2004) commented path method to distinguish and evaluate the actions and transformations carried out by the collective of students engaged in the research during the course. This methodology Allows to analyze the environment through the observation and recurrences and / or differences identified in excerpts from the workshops and the transcripts of comments of the course, referring to the direct experience of the students in the moments in which they dedicate themselves to the project in progress in the school of collection and forwarding of the trash Electro-electronic. As a result of the research, we were able to distinguish changes in the ways of perceiving the problem of electro-electronic waste in the students' experience, knowledge and knowledge that can contribute with advances in the experience of Environmental Education focused on contemporary problems, produce changes in actions directed to the treatment of electronic and electronic waste The students' experience in school and the strengthening of public policies aimed at the treatment of electronic waste, based on the experience of a group of students from a secondary school in Limoeiro do Norte
Method of taking care of eletroeletronic waste: analyzing changes in students' actions in environmental workshops at Lauro Rebouças de Oliveira high school in Limoeiro do Norte-CE
Keywords: Resíduos Eletroeletrônicos; Relação Humano-Técnica; Educação Ambiental; Sustentabilidade; Electrical and Electronic Waste; Human-Technical Relation; Environmental Education; Sustainability; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE